(3JQLeI GdSjO YHOGddg THQs - (3eMeO eYUhes ((3YHGS Hf eMeO THQ s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf GdPj QaY bOQ GdYdeGA Edi CYdi Ydjjf s
(3BNQgG (B:s
(3agPg NdGUI GdcdGe ajeG PcQfG ef CMhGd SjOfG hehdGfG , hGdMeOddg QH GdYGdejf hUdi Gddg Ydi eMeO hBdg GdWjHjf GdWGgQjf Ydjge CaVd UdGI GdoeUdjf s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B108 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdYdejI GdTHQjI (B- (3GdHUQI (B(8) s
Keywords: (3GdJGQjNs